ACADEMIC DISCIPLINES IN THE EDUCATION OF DECORATIVE AND APPLIED ART`S SPECIALISTS: DRAWING - Білий, В. Д. (Art and Design, 2021)
Purpose: to analyze the value of theoretical and practical knowledge and skills obtained in the study of Academic Drawing by students of the Decorative and Appling Art`s Department of the Kosiv Institute of Applying and Decorative Art LNAA. Methodology. Analytical and comprehensive approaches to the subject of research, structural analysis, observation and modeling methods, as well as comparative analysis were used, which made it possible to identify the features of drawing techniques` using in the realization of decorative and applied art projects. Results. The importance of the Drawing in the process of creating and making of decorative and applied art`s projects has been determined. It was revealed that for the realization, analysis of the form, its design (architectonics) and material is of particular importance, while the graphic means characteristic of a drawing is most often used to apply an ornament to the surface of the item. It is also important to sketching, aimed at theoretical comprehension of existing forms; search for new forms and designs in accordance with the previous idea. Special attention to the importance of the drawing in the education of students’ aesthetic ideas and the creation of artistic and expressive works of art is paid. Scientific novelty of the paper lies in identifying the theoretical and practical skills and abilities that students of decorative and applied art`s specialties receive in the study of Academic Drawing and how they use them in the creating projects and art works based on the Kosiv Institute of Applying and Decorative Art LNAA. Practical significance. The obtained results into account in the process of teaching special disciplines can be taken, developing guidelines for them, in further scientific research.